Adopting Local Languages as Official Languages: Effect on Women and Rural Individuals’ Labor Force in Burkina Faso - SOULEYMANE YAMEOGO (KDI Journal of Economic Policy, 2020)
This study investigates the impact of the use of the main local languages in Burkina Faso (Moore, Dioula, Fulfulde) on labor force participation. Using Ethnologue language data, I compute the relative language distance reduction index, after which I use a probit/logit model and instrumental variable approach to account for language use policy endogeneity. This study finds that the use of the Moore language increases the likelihood of labor force participation by 36 percent, with a strong impact on women at 59 percent, nine times higher than men, and 38.3 percent for rural individuals, five times higher than individuals living in urban areas. The Dioula language exhibits comparable trends, while Fulfulde has a negative impact on individuals. The study recommends the use of local language(s) as official language(s) to improve labor force participation. However, a bilingual approach combining local and international language(s) will be of use to account for globalization and international competitiveness. The findings here may be of use to researchers and policymakers as part of their effort to increase the labor force participation rates of women and rural individuals. Moreover, this research has significant implications with regard to the implementation of language use policies in a variety of postcolonial language contexts.